2018
DOI: 10.1016/j.jtcvs.2018.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valvular dynamics and 3-dimensional geometry in awake and anesthetized sheep

Abstract: General anesthesia did not alter tricuspid annular or subvalvular 3-dimensional geometry but reduced right ventricular contraction and tricuspid annular dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…After 1 week of recovery, the tricuspid valve was studied while the sheep were awake and then studied again with the sheep under general anesthesia. Jazwiec and colleagues 8 found that general anesthesia (1) was not associated with any substantial changes in systemic or pulmonary hemodynamics, (2) decreased systolic contraction of the tricuspid valve annulus secondary to decreased contraction of the septal portion of the annulus, (3) did not change the geometry of the right ventricle and subvalvular apparatus, (4) depressed the contractility of the free wall of the right ventricle, and (5) increased the severity of tricuspid regurgitation. Because there is no change in the geometry of the subvalvular apparatus, tricuspid regurgitation is likely related to decreased annular contraction during systole.…”
Section: Juan a Crestanello MDmentioning
confidence: 99%
See 2 more Smart Citations
“…After 1 week of recovery, the tricuspid valve was studied while the sheep were awake and then studied again with the sheep under general anesthesia. Jazwiec and colleagues 8 found that general anesthesia (1) was not associated with any substantial changes in systemic or pulmonary hemodynamics, (2) decreased systolic contraction of the tricuspid valve annulus secondary to decreased contraction of the septal portion of the annulus, (3) did not change the geometry of the right ventricle and subvalvular apparatus, (4) depressed the contractility of the free wall of the right ventricle, and (5) increased the severity of tricuspid regurgitation. Because there is no change in the geometry of the subvalvular apparatus, tricuspid regurgitation is likely related to decreased annular contraction during systole.…”
Section: Juan a Crestanello MDmentioning
confidence: 99%
“…The effects of cardiopulmonary bypass were not studied by Jazwiec and colleagues. 8 Nonetheless, it is important to highlight that cardiopulmonary bypass and aortic crossclamping would likely exacerbate tricuspid regurgitation even further and perhaps more profoundly than general anesthesia alone. Cardiopulmonary bypass may adversely affect the severity of tricuspid regurgitation through several mechanisms, including (1) increased pulmonary vascular resistances and right ventricular afterload; (2) right ventricular dysfunction secondary to ischemia reperfusion, stunning, air embolization into the right coronary artery, or inadequate myocardial protection; and (3) abnormal interventricular septal motion.…”
Section: Juan a Crestanello MDmentioning
confidence: 99%
See 1 more Smart Citation
“…We used Smoothed Particle Hydrodynamics (SPH) [15] to simulate the effects of MC location on TV closure and regurgitation. Although there are a few numerical studies that focused on the TV [16][17][18], this is the first study that simulated the effects of MC on TR using an FSI model. Once validated [19], the results of this study would have potential clinical implications for optimal MC treatment for TR.…”
Section: Introductionmentioning
confidence: 99%
“…To address this problem, Malinowski and colleagues 1 have developed a human model that uses ex vivo perfusion and surgically implanted sonomicrometry crystals, a protocol previously used in animal models. 2,3 Crystals implanted along the tricuspid annulus, right ventricular free wall, and right ventricular apex provide dynamic anatomic detail, while pressure transducers placed in the right atrium and ventricle provide hemodynamic data. Harvested hearts rejected for transplant, with no greater than mild right ventricular dysfunction or mild tricuspid regurgitation, are connected to an ex vivo perfusion system.…”
mentioning
confidence: 99%